2000
DOI: 10.1002/1097-4628(20001205)78:10<1721::aid-app20>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiblock copolymers based on segments of poly (D,L-lactic-glycolic acid) and poly(ethylene glycol) or poly(?-caprolactone): A comparison of their thermal properties and degradation behavior

Abstract: A comparison of the thermal properties of two classes of poly(D,L‐lactic‐glycolic acid) multiblock copolymers is reported. In particular, the results of differential scanning calorimetry, and thermogravimetric analysis of copolymers containing poly(ethylene glycol) (PEG) or diol‐terminated poly(ϵ‐caprolactone) (PCDT) segments are described. The influence of the chemical structure and the length of PEG and PCDT on thermal stability, degree of crystallinity and glass transition temperature (Tg ) is discussed. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…This behavior was observed by other authors, who found a T g for pure PLGA of 46.8°C, 11 which disappeared when PLGA–PCL was used. This phenomenon was due to the fact that this endothermic effect was overlapped by the melting peak of PCL, which took place in the same temperature range 14…”
Section: Resultsmentioning
confidence: 99%
“…This behavior was observed by other authors, who found a T g for pure PLGA of 46.8°C, 11 which disappeared when PLGA–PCL was used. This phenomenon was due to the fact that this endothermic effect was overlapped by the melting peak of PCL, which took place in the same temperature range 14…”
Section: Resultsmentioning
confidence: 99%
“…No primeiro estágio ocorreu a degradação a partir das terminações das cadeias dos blocos PLAs, favorecida pela formação de éster cíclico lactídeo, e no segundo estágio, a alta temperatura, ocorreu a cisão térmica da cadeia polimérica. O comportamento térmico foi previamente relatado para polímeros amorfos preparados a partir de (d,l) lactídeo e seus copolímeros [17][18] .…”
Section: Resultsunclassified
“…creep or stress relaxation or by small amplitude oscillation tests [23][24][25][26]. The chemical nature [23,24] and the thickness of the adhesive influence the adhesive performances as well as the surface conditions of the adherent including roughness and surface tension.…”
Section: Introductionmentioning
confidence: 99%
“…creep or stress relaxation or by small amplitude oscillation tests [23][24][25][26]. The chemical nature [23,24] and the thickness of the adhesive influence the adhesive performances as well as the surface conditions of the adherent including roughness and surface tension. In fact the surfaces of tape and backing and the bulk properties of adhesives effects are coupled and it *Address correspondence to this author at the Department of Industrial and Information Engineering, Second University of Naples, Italy; Tel: +39 081 5010 295; Fax: +39 081 5010 412; E-mails: giuseppe.lamanna@unina2.it, giuseppe.lamanna.ff@gmail.com would be more accurate to consider adhesive/substrate pairs than adhesives and substrates separately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation